UMP bonds with Media in friendly bowling competition - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) recently held a friendly bowling tournament with members of the Press, extending the university’s appreciation for the latter’s efforts in providing ample media exposure about UMP over the years.